2018
DOI: 10.1038/s41598-018-26414-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinctiveness in virological features and pathogenic potentials of subgenotypes D1, D2, D3 and D5 of Hepatitis B virus

Abstract: Distinct clinical features of HBV infection have been associated with different viral genotype/subgenotype. HBV Genotype-D comprised of 10 subgenotypes, D1–D10, whose clinical implications still remain elusive. We investigated for the first-time, the virologic characteristics and cytopathic effects of four non-recombinant D-subgenotypes, D1/D2/D3/D5. Expressions of viral/host genes were evaluated in Huh7 cells transfected with full-length, linear-monomers of HBV/D-subgenotypes or pGL3-Basic vector carrying sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
1
9
0
1
Order By: Relevance
“…Our data showed that serum HBcrAg level was significantly associated with younger age, HBeAg positivity, higher HBV-DNA titers, and high qHBsAg level, but not HBV genotypes. As noted earlier, the HBV genotype might depend on the biogeography, and not be affected by any host or viral proteins, but can influence the progression of liver disease[33-35]. Our results confirmed that there was no independent association between HBV genotype and serum HBcrAg level, indicating that HBV-triggered liver injury is mediated by host immune response to viral proteins[33].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data showed that serum HBcrAg level was significantly associated with younger age, HBeAg positivity, higher HBV-DNA titers, and high qHBsAg level, but not HBV genotypes. As noted earlier, the HBV genotype might depend on the biogeography, and not be affected by any host or viral proteins, but can influence the progression of liver disease[33-35]. Our results confirmed that there was no independent association between HBV genotype and serum HBcrAg level, indicating that HBV-triggered liver injury is mediated by host immune response to viral proteins[33].…”
Section: Discussionsupporting
confidence: 87%
“…As noted earlier, the HBV genotype might depend on the biogeography, and not be affected by any host or viral proteins, but can influence the progression of liver disease[33-35]. Our results confirmed that there was no independent association between HBV genotype and serum HBcrAg level, indicating that HBV-triggered liver injury is mediated by host immune response to viral proteins[33]. Interestingly, we found that patients with BCP/PC mutation had a significantly lower serum concentration of HBcrAg when compared with their wild-type counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Serum örnekleri: Biyopsi örnekleri ile eş zamanlı ve normal kan alma (venöz) prosedürü uyarınca uygun tüplere alınan hasta kan örnekleri santrifüj edilerek serumları ayrıldıktan sonra steril ependorf tüplere transfer edilerek laboratuar çalışmaları için -80 • C'de muhafaza edilmiştir. HBV/D'nin çoklu coğrafik yayılım ve yüksek heterojenite içeren genotiplerden biri olması, daha yüksek oranda S gen mutasyon/varyasyon içermesi, HBV/D3'ün OBI'li bireylerde diğer subgenotiplere oranla daha fazla varyasyon içerdiği, kronik hepatit B hastaları arasında ise diğer subgenotiplere oranla daha az HBV DNA yükü, daha yavaş hastalık progresyonu ve daha düşük onkojenik potansiyel ile daha düşük replikasyon kapasitesi ile karakterize olduğu yönündeki veriler bu yaklaşımı destekler niteliktedir (30)(31)(32). HBV/D3 subgenotopinin bazı coğrafik bölgelerde HBsAg seronegatif kan donörleri ile OBI için risk faktörü olarak kabul edilen damar içi uyuşturucu kullananlar ve madde bağımlıları ile HIV ile ko-enfekte OBI vakalarında daha sık tespit edildiğine dair veriler de HBV/ D3'ün OBI ile ilişkili olabileceğine işaret etmektedir (33).…”
Section: Discussionunclassified
“…One study with Alaskan natives reported that genotype C2 and F develop HCC more than genotype A2, B6, and D ( McMahon, 2009 ). In India, subgenotypes D1 and D3 have been found to be associated with advanced diseases though D2 showed highest replication efficiency ( Datta et al, 2018 ; Khatun et al, 2018 ). Although genotype D has been reported as an independent risk factor for fulminant hepatitis ( Thukar et al, 2002 ; Wai et al, 2005 ), genotype G is rarely seen alone.…”
Section: Life Cycle Of Hbv Through Rna Intermediates: a Key To Disease Pathogenesismentioning
confidence: 99%